Compliance and Initiative in the Production of Safety (Springer Nature, 2024)
This open access book addresses the idea that there are two ways to go about achieving a safe working environment. The text challenges the prevailing notion that compliance with a rule system, imposed from the top of an organization and designed to anticipate possible hazards in system operation, is really incompatible with the idea that the professional expertise of front-line workers is what promotes safe outcomes despite inevitable unanticipated perturbations. The contributors, drawn from academic and industrial backgrounds, demonstrate that rather than being at odds with each other, rules-compliance and proactivity are in fact complementary resources the coexistence of which increases safety. Furthermore, the implications of this approach extend beyond safety, being relevant to business performance, strategies for innovation and system resilience as well. The book steps back from an exclusive focus on front-line work to explore the way in which compliance and initiative are articulated at different levels within the hierarchy of a firm, right up to that of top management. Further, the contributors analyze the way in which safety authorities, the justice system, and the general public perceive and interpret such strategies, in particular in the aftermath of major events. This book deals with issues of interest to researchers and graduate students in safety science and organization studies and to members of expert bodies and experts in industry and consultancy concerned with similar subjects. ; ​